Penerapan Teknologi Budidaya Inpago Unsoed 1 di Kelompok Tani Padi Desa Tinggarjaya, Kecamatan Jatilawang, Kabupaten Banyumas - Riyanto, Agus; Widiatmoko, Teguh (Universitas Darussalam Gontor, 2019)
Tegaljaya and Mekarjaya are farmer groups in Tinggarjaya Village, Jatilawang District, Banyumas Regency. The narrow land area causes the welfare of farmer groups members to be still low. In order to improve well-being, it is necessary to increase rice productivity using high yield and high quality varieties, namely Inpago Unsoed 1. The purpose of this activity is to increase rice production in Tinggarjaya Village through the application of Inpago Unsoed 1 cultivation technology. This activity was carried out through the Inpago Unsoed 1 Rice Crop Management Field School approach which was translated into three activities, namely 1) Technology Transfer; 2) Plotting Demonstration; and 3) Evaluation of activities. The results of this activity were farmers of the Tegaljaya and Mekarjaya Farmers who received the Inpago Unsoed 1 superior variety and were willing to replan and the farmer gets a new superior variety alternative, Inpago Unsoed 1 which has good competitiveness.